Free objects in the category of geometries - Talal Ali Al-Hawary (International Journal of Mathematics and Mathematical Sciences)
The aim of this note is to introduce the class of free geometries purely in terms of morphisms. Several classes of well-known matroid morphisms are characterized via the new concept.